An Investigation into the Effective Removal of VOCs Released from Wood Drying using Rare Metal‐Organic Frameworks. Issue 9 (18th February 2022) - Hu, Zichu; An, Yuhong; Zhang, Wanqi; Zhong, Yuan; Chen, Zhangjing; Wang, Boyun; Wang, Sunguo; Wang, Qiang; Li, Xinran; Zhang, Xiaotao; Wang, Ximing
Abstract: This work reported the synthesis of Ce‐MOF and Nd‐MOF adsorption materials using the solvothermal method with the rare earth metals Ce 3+ and Nd 3+ as the particle center and discussed the adsorption effect of the two synthesized nanomaterials on the VOCs released by dry wood. The porous morphology of the material increases the benzene gas contact area. The maximum adsorption capacity of benzene, according to the Langmuir model, is 128.98 mg/g and 132.22 mg/g, respectively. The method has a large adsorption capacity, good adsorption effect, non‐toxic and harmless, low recycling cost, recyclable multiple times, simple operation, stable structure, no secondary environmental pollution, etc., and has good application prospects in the wood drying industry. Abstract :